2020
DOI: 10.1186/s12883-020-01960-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brain-computer interface training based on non-invasive electroencephalography using motor imagery on functional recovery after stroke - a systematic review and meta-analysis

Abstract: Background Training with brain-computer interface (BCI) technology in the rehabilitation of patients after a stroke is rapidly developing. Numerous RCT investigated the effects of BCI training (BCIT) on recovery of motor and brain function in patients after stroke. Methods A systematic literature search was performed in Medline, IEEE Xplore Digital Library, Cochrane library, and Embase in July 2018 and was repeated in March 2019. RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
(96 reference statements)
1
35
0
Order By: Relevance
“…BCI can also be used to improve visuospatial abilities. Tonin et al [86] have shown that BCI can improve laterally dominant attentional visuospatial deficits. By using covert visual spatial attention-(CVSA-) BCI in three patients with left spatial neglect (SN) stroke, they found that the patients could control CVSA-BCI with accuracy rates above 50%.…”
Section: Memory Functionmentioning
confidence: 99%
“…BCI can also be used to improve visuospatial abilities. Tonin et al [86] have shown that BCI can improve laterally dominant attentional visuospatial deficits. By using covert visual spatial attention-(CVSA-) BCI in three patients with left spatial neglect (SN) stroke, they found that the patients could control CVSA-BCI with accuracy rates above 50%.…”
Section: Memory Functionmentioning
confidence: 99%
“…In addition to neuroprosthetics, the use of MI-based BCIs attracted considerable interest also as a potential neurorehabilitation technique to restore motor function after stroke [ 38 , 58 , 59 ]. Indeed, the scientific interest in the use of robotics in rehabilitation scenario is increasing considerably due to the growing number of people requiring rehabilitation following problems such as stroke and, at the same time, to the insufficient number of therapists available to deliver rehabilitation protocols to patients [ 59 ].…”
Section: Brain–computer Interfaces Classifications and Applications: A Synthetic Overviewmentioning
confidence: 99%
“…Brain-computer interface (BCI) is a direct connection path established between the human brain and external devices. This technology translates the neurophysiological signals in the brain into control signals that can operate external devices or computers to assist in performing different tasks [ 39 ]. The accuracy of the cortical signals obtained by noninvasive BCI systems is not as high as the signals from invasive BCI [ 40 ], but portability, safety, comfort, and low cost make noninvasive BCI the first choice for obtaining relevant brain electrical signals and electroencephalogram (EGG) [ 41 ].…”
Section: Brain-computer Interface (Bci)mentioning
confidence: 99%